Effect of storage on metabolites of brown rice. (22nd June 2020) - Wang, Changyuan; Feng, Yuchao; Fu, Tianxin; Sheng, Yanan; Zhang, Shu; Zhang, Yiwei; Jiang, Yingjun; Yu, Miao; Zhang, Dongjie
Abstract: Background: Storage is an essential part of brown rice circulation. During the storage process, the metabolic activity of brown rice is still ongoing, and long‐term storage leads to the deterioration of brown rice. Metabolomics analysis was performed using gas chromatography–mass spectrometry to investigate the changes in metabolites of brown rice after storage at 18 °C for 12 months. Results: In terms of quantity, sugar, fatty acids, and other metabolites in brown rice decreased after storage, and alcohols, aldehydes, phenols, and amines increased. A total of 34 differential metabolites were screened. In terms of contents, carbohydrates, amino acids, and fatty acids of brown rice decreased after storage, while those of sugar alcohol, amines, and aldehydes increased after storage. Cluster analysis of the samples at zero storage time revealed that the metabolites expressed least became highly expressed after storage and those expressed highly became low after storage. Metabolic pathway analysis showed that storage significantly influenced the lipid metabolism in brown rice. Palmitoleic acid, cholesterol, linoleic acid, and lauric acid are four key metabolites in lipid metabolism during storage of brown rice. Conclusion: Significant changes occurred in quantity and type of brown rice metabolites after storage. Storage has the greatest effect on lipids. Storage caused a 'reverse change' in the metabolites content of brown rice. The results obtained may help in understanding the changes in metabolites profile and delaying of the quality deterioration of brown rice during storage.